Effects of the FIFA 11+ injury prevention programme on muscle strength and landing biomechanical markers of ACL injury during fatigue among youth soccer players - Bukry Saiful Adli; Justine Maria; Azidin Raja Mohammed Firhad Raja; Azhar Noor Izzati; Zolkafi Mohd Azrul Anuar; Lo Chi Ngai; Manaf Haidzir (Biomedical Human Kinetics)
Study aim: This study aimed to investigate the effect of the FIFA 11+ injury prevention programme on strength and on muscle strength and landing biomechanical markers of anterior cruciate ligament (ACL) injury during fatigue among youth recreational soccer players.